2007
DOI: 10.1002/masy.200750505
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Responsive PNIPAAm Copolymers with Hydrophobic Spacers

Abstract: Summary:We have synthesised and characterised three sets of acryloyl(amino-acid)/ NIPAAm co-polymers. Three different co-monomers were synthesised and copolymerized with N-isopropylacrylamide (NIPAAm) by free radical polymerization in different molar ratios (12:1, 9:1, and 6:1). All series contain aliphatic spacers and are carboxylic terminated. The effect of co-monomer nature and content on the glass transition and the LCST transition in solution has been investigated. The main factor affecting the glass tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This is because, when the samples are heated to temperature above LCST, some additional intersegment hydrogen bonds are formed between the collapsed chains; thus, during cooling this chain, dissociation occurs only when the temperature is lower than the LCST. Similar observations have been made by several researchers on NIPAAm-based polymers; [22][23][24][25][26][27][28] Cheng et al 25 confirmed the presence of additional hydrogen bonds during polymer heating by FTIR analysis where the intensity for hydrogen bonding between polymer PHEMA and grafted P(HEMA-g-(NIPAAm-coAAm)) hydrogel synthesis PHEMA samples, which are solid and transparent, were successfully synthesized in the method discussed in the Experimental section. In the highly cross-linked PHEMA hydrogels, an increase in crosslinking density created samples that were more rigid and had lower swelling ratios.…”
Section: Oligomer Lcstssupporting
confidence: 76%
“…This is because, when the samples are heated to temperature above LCST, some additional intersegment hydrogen bonds are formed between the collapsed chains; thus, during cooling this chain, dissociation occurs only when the temperature is lower than the LCST. Similar observations have been made by several researchers on NIPAAm-based polymers; [22][23][24][25][26][27][28] Cheng et al 25 confirmed the presence of additional hydrogen bonds during polymer heating by FTIR analysis where the intensity for hydrogen bonding between polymer PHEMA and grafted P(HEMA-g-(NIPAAm-coAAm)) hydrogel synthesis PHEMA samples, which are solid and transparent, were successfully synthesized in the method discussed in the Experimental section. In the highly cross-linked PHEMA hydrogels, an increase in crosslinking density created samples that were more rigid and had lower swelling ratios.…”
Section: Oligomer Lcstssupporting
confidence: 76%
“…However, it is possible to modify the LCST of a thermosensitive hydrogel by introducing the appropriate monomer moieties. The bulk copolymerization of a main thermosensitive monomer and another comonomer that modulates the LCST of the resulting polymer has been extensively studied, allowing the thermosensitive polymer to be engineered according to specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] In addition the LCST of PNIPAAm can be tuned easily to a desired temperature by incorporating a suitable comonomer. [22][23][24][25] The peptide selected is the ionic complementary octa-peptide FEFEFKFK, where F is phenylalanine, E is glutamic acid and K is lysine. This peptide is known to form a three-dimensional beta-sheet rich fibrillar hydrogel at 30 g L À1 in water, at room temperature and its gelation is reversible; the gel melting at B75 1C.…”
mentioning
confidence: 99%